BIOLOGICAL AND ECOLOGICAL PECULIARITIES OF SAMBUCUS NIGRA IN THE CONDITIONS OF THE LEFT BANK DNIEPER - Fedko, R. M.; Antonets, M. O.; Antonets, O. A.; Viblyi, O. M. (Scientific Progress & Innovations, 2021)
The introduction of rare fruit and berry plants to the culture is associated with the need to improve horticultural products' therapeutic and dietary qualities. Non-traditional fruit plants contain a large number of biologically active substances with antioxidant activity. This is especially true during the COVID-19 pandemic. Among such plants in the medicinal plant growing of Ukraine, the distribution of elderberry is of strategic importance. White and fragrant flowers of elderberry, young shoots, fresh leaves, berries are widely used in phytomedicine. Under natural conditions, this plant is known as a shrub species. Therefore it should be considered as a promising crop in the formation of field-protective forest plantings. The research is aimed at studying the biological and ecological features of elderberry model samples in the natural conditions of the Left Bank of the Dnieper. The research was conducted in 2021 on the territory of the arboretum of the Research Station of Medicinal Plants of the Institute of Agroecology and Environmental Management of the National Academy of Agrarian Sciences of Ukraine. Among the total number of plants, five model samples of 5–6 years of age were selected, which began to generate intensively and grow in different lighting conditions. An important factor for the collection of raw elderberry is its physical availability. Therefore, the assessment of biological and technological yield of inflorescences and fruits was carried out. For this purpose, the crown was conditionally divided into three technological layers. Thus, the effect of lighting was established on morphological features and productivity of model plants 5–6 years of age. The first and second model samples of elderberry in the light 90,000–130,000 lux had the best indicators in plant height, crown projection diameter, and productivity. Studying the dynamics of generative organs’ formation within the technical layers during the period of flowering and fruit set, the largest number of formed inflorescences was observed on the second and third technological layers among all model samples. Moreover, the largest number of inflorescences and collective fruit was formed in the first and second model samples. Plants that grow in well-lit areas and have high rates of generative organ formation are offered for analytical selection. This basic material of elderberry can be recommended for seed and vegetative propagation.